Pemanfaatan Media Gambar Animasi berbasis PowerPoint untuk Meningkatkan Kemampuan Membaca Permulaan Siswa Sekolah Dasar - Muhammad Ilham; Ragil Desinatalia (Institut Agama Islam Negeri Kendari, 2022)
This classroom action research aims to examine the portraits of early reading learning, the application of early reading learning by using PowerPoint animation media, and the use of this media in improving students' early reading skills at one of elementary school at Wawonii Tenggara, Southeast Sulawesi. The results of qualitative analysis showed that the form of learning to early reading at the school was conducted in a simple way i.e. by writing letters of the alphabet on the blackboard and pronouncing the letters aloud together. The activities of teachers and students in learning have shown a good increase from cycle to cycle. Teachers find it easier to manage classes, direct students, and focus students on learning, meanwhile students seem more confident to ask questions and make presentations in front of the class. The use of PowerPoint animated image media has been proven to be able to help students improve their beginning reading skills.Keywords: Beginning reading; powerpoint animation media; elementary school